2018
DOI: 10.9734/cjast/2018/44358
|View full text |Cite
|
Sign up to set email alerts
|

Prospects and Problems of Brain Computer Interface in Healthcare

Abstract: Brain-Computer Interface (BCI) otherwise known as a Brain-Machine Interface (BMI) is an emergent technology whose goal is to create a real-time and direct communication pathway between the brain and external devices such as computers, robots, artificial limbs and wheelchairs. In BCI, cerebral or brain activities control these devices by transmitting and receiving signals from the brain. BCI is applied in healthcare to improve the communication capabilities of people living with disabilities or locked in syndro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 44 publications
(74 reference statements)
0
4
0
Order By: Relevance
“…This feeling of eeriness has been described and named the “Uncanny Valley” by Mori (1970) [ 59 ]. Mori observed that robots appeal more to people with a human-like appearance, but only up to a certain point [ 59 , 60 ]. After reaching the uncanny valley, a person’s affinity decreases into a feeling of unease and a tendency to become scared.…”
Section: Discussionmentioning
confidence: 99%
“…This feeling of eeriness has been described and named the “Uncanny Valley” by Mori (1970) [ 59 ]. Mori observed that robots appeal more to people with a human-like appearance, but only up to a certain point [ 59 , 60 ]. After reaching the uncanny valley, a person’s affinity decreases into a feeling of unease and a tendency to become scared.…”
Section: Discussionmentioning
confidence: 99%
“…As for augmenting our bodies and brains, a growing literature has shown that it is not necessarily so easy to live with ones prostheses (e.g. Davies and Dattta, 2003) and the use of brain/computer interfaces requires extensive training and is exhausting for the user over any long period (Olaronke et al, 2018). Many who have electrodes implanted for deep brain stimulation to modulate mobility problems cause by Parkinson’s, and now to ‘treat’ depression, ask for them to be turned off as they dislike the effects they have on their own sense of personhood (Bluhm et al, 2020; Dubiel, 2009).…”
Section: Part One: a Badly Formed Problemmentioning
confidence: 99%
“…Lastly, BCI systems are exposed to possible misuse and cyberattacks, which can easily result in intentional or unintentional alteration of their functioning 18 .…”
Section: 3mentioning
confidence: 99%